Voter Turnout and Crisis of Legitimacy: A Critical Analysis of General Elections in Nigeria’s Fourth Republic (1999-2023) - Adebogun Babatunde Olayinka; Gabriel Lola Oriloye; Abraham Edeh; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2024)
Electoral democracy provides an impetus for citizens’ participation and the act of choosing political actors across different democracies. Nigeria had transitioned from one civilian administration to another, beginning in 1999 and lasting until 2023. However, the practice of democracy and the conduct of elections appeared challenged even though the electorate “elects” the candidate of their choice in every election circle. Issues such as the imposition of candidates, violence, rigging, and a decline in voter turnout remain major issues of public concern. Previous studies have shown the challenges or factors affecting the conduct of free, fair, and credible elections, which include electoral rigging, imposition of candidates, violence, and low voter turnout, but they have not sufficiently shown how these factors affect the outcome of the election and the legitimacy of the regime change. This study examined how voter participation influenced the crisis of legitimacy in Nigeria’s fourth republic elections. In conducting this investigation, the perspective of theorists was delved into as the theoretical foundation of this study, relying on a qualitative approach, using secondary data, and analyzing via content and historical analysis. The study found that low voter turnout influenced the legitimacy of the regime change. The paper recommended that the electoral body and civil society organizations should be more involved in voter education in order to encourage voter turnout and confer legitimacy on the regime change.